(untitled) (Altre Modernità, 2011)
Slavery, which plaid a significant role in several ancient civilizations around the world, was supported by philosophers, theologians and popes. Even if its importance has been underestimated, the presence of black women and men is stated from the first expeditions to the River Plate (many times, by means of illegal traffic). Led by bishop Vitoria, that traffic increased since the late 16th century. Black women were often sexually exploited but, instead of paying attention to their problems, much of the literature has ignored them or has created an archetypal woman, characterized by beauty, sensuality and eroticism. With some exceptions, this image remains in our days.